The Dramaturgy of Da’wah for Religious Communicatorsin Muslim Minority Communities - Kohar, Wakidul; Kustati, Martin; Jemkhairil, Jemkhairil; Ashadi, Andri; Aqil, Muhammad; Saka, Putri Ananda; Alfred , Alfred (SCAD Independent, 2025)
Da’wah strategies continue to evolve in collaboration with societal trends and receptivity. A dissonance between societal developments and the methods of religious propagation may result in the rejection of religious messages and strained interactions between majority and minority groups. Therefore, a more contextualized approach is required to enhance the effectiveness of da’wah. This study explored dramaturgical da’wah as a strategic framework employed by religious communicators to convey religious messages through frontstage and backstage performances. Utilizing a qualitative methodology, data were collected through interviews and observations of Muslim minority preachers on Nias Island. The findings demonstrated that da’wah practices were implemented by following dramaturgical principles, engaging audiences differently across stages. The success of this strategy was influenced by segmented communication methods, cultural adaptation to local traditions, and the portrayal of Islam as peaceful and open to interfaith dialogue. This approach contributed to fostering interreligious harmony and sustaining the presence of Muslim minorities in Nias. The study offers a novel perspective, highlighting that the development of da’wah strategies must consider the field of experience, particularly in regions where Muslims are a minority.